2005
DOI: 10.1186/ar1840
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: CD3+CD4+CD28null and CD3+CD8+CD28null T cells are enriched in patients with immune-mediated diseases compared with healthy controls. This study shows that CD4+CD28null T cells express Toll-like receptors recognizing bacterial lipopolysaccharides in ankylosing spondylitis, psoriatic arthritis and rheumatoid arthritis. In ankylosing spondylitis, TLR4 (23.1 ± 21.9%) and, to a smaller extent, TLR2 (4.1 ± 5.8%) were expressed on CD4+CD28null T cells, whereas expression was negligible on CD4+CD28+ and CD8+ T cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Another feature of CD28 − T-cells is their longevity and persistence that can be explained by defects in the apoptotic pathway with upregulation of bcl-2 and Fas-associated death domain like IL-2-converting enzyme-like inhibitory protein (FLIP) (66, 67). Terminally differentiated T-cells also acquire new stimulatory receptors including killer cell immunoglobulin-like receptors (KIRs) and Toll-like receptors (TLRs) (68, 69). Thus, activation of CD4 + CD28 − T-cells no longer depends on professional antigen-presenting cells, rather it is promoted by stress molecules as well as bacterial and/or viral products (65).…”
Section: Development and Cellular Senescence Of Tregsmentioning
confidence: 99%
“…Another feature of CD28 − T-cells is their longevity and persistence that can be explained by defects in the apoptotic pathway with upregulation of bcl-2 and Fas-associated death domain like IL-2-converting enzyme-like inhibitory protein (FLIP) (66, 67). Terminally differentiated T-cells also acquire new stimulatory receptors including killer cell immunoglobulin-like receptors (KIRs) and Toll-like receptors (TLRs) (68, 69). Thus, activation of CD4 + CD28 − T-cells no longer depends on professional antigen-presenting cells, rather it is promoted by stress molecules as well as bacterial and/or viral products (65).…”
Section: Development and Cellular Senescence Of Tregsmentioning
confidence: 99%
“…TLR5 ligand flagellin and TLR7/8 ligands resiquimod (R-848) also enhance T cell proliferation and IFN-production in human CD45RO+ T cells [114]. Perforin production is stimulated by LPS in TLR4-positive CD28-CD4+ T cells [125]. When stimulated with TLR3 ligand polyI:C and TLR9 ligand CpG DNA, CD4+ T cells survive longer although there is no increase in proliferation [126].…”
Section: Tlr Expression On T Cellsmentioning
confidence: 97%
“…Moreover, certain cytokines such as TNF have been shown to increase the expression of TLRs [35]. Indeed, serum and synovial fluid levels of p40 IL-12/IL-23 have been shown to be increased in SpA compared with osteo arthritis patients [36].…”
Section: Consequences Of Tlr Activationmentioning
confidence: 99%
“…showed that this subpopulation of T cells from SpA patients significantly expressed more functionally active TLR4 and 2 compared with controls. These levels decreased significantly with anti-TNF treatment [35]. …”
Section: Consequences Of Tlr Activationmentioning
confidence: 99%
See 1 more Smart Citation